TPL-2 Regulates Macrophage Lipid Metabolism and M2 Differentiation to Control TH2-Mediated Immunopathology. - Yashaswini Kannan; Jimena Perez-Lloret; Yanda Li; Lewis J Entwistle; Hania Khoury; Stamatia Papoutsopoulou; Radma Mahmood; Nuha R Mansour; Stanley Ching-Cheng Huang; Edward J Pearce; Luiz Pedro S de Carvalho; Steven C Ley; et al. (PLoS Pathogens)
Persistent TH2 cytokine responses following chronic helminth infections can often lead to the development of tissue pathology and fibrotic scarring. Despite a good understanding of the cellular mechanisms involved in fibrogenesis, there are very few therapeutic options available, highlighting a significant medical need and gap in our understanding of the molecular mechanisms of TH2-mediated immunopathology. In this study, we found that the Map3 kinase, TPL-2 (Map3k8; Cot) regulated TH2-mediated intestinal, hepatic and pulmonary immunopathology following Schistosoma mansoni infection or S. mansoni egg injection. Elevated inflammation, TH2 cell responses and exacerbated fibrosis in Map3k8-/-mice was observed in mice with myeloid cell-specific (LysM) deletion of Map3k8, but not CD4 cell-specific deletion of Map3k8, indicating that TPL-2 regulated myeloid cell function to limit TH2-mediated immunopathology. Transcriptional and metabolic assays of Map3k8-/-M2 macrophages identified that TPL-2 was required for lipolysis, M2 macrophage activation and the expression of a variety of genes involved in immuno-regulatory and pro-fibrotic pathways. Taken together this study identified that TPL-2 regulated TH2-mediated inflammation by supporting lipolysis and M2 macrophage activation, preventing TH2 cell expansion and downstream immunopathology and fibrosis.